Pelatihan Karakter Building Dan Mental Imagery Bagi Atlit PPLP Sumatera Barat - Nurul Ihsan; Syahrastani Syahrastani (Jurnal Berkarya Pengabdian Masyarakat, 2019)
Character is a process that is continuously carried out to form, character, character, and mental characteristics that are based on the spirit of devotion and togetherness. Fostering characters that display conducive characters in social, national and state life based on the values ​​of the Pancasila philosophy. Mental image is the ability of humans to imagine images in the mind after the original stimuli can no longer be seen. This cognitive component is one of the ways that help factors in existing memories and thoughts. This component provides explanations to help translate the concepts introduced. Every athlete is always confronted with a variety of discussions about achievement, but not all talks and related achievements are supported by various factors not only technical and physical but also the character and mental. This is intended so that everyone has a strong character and also has a good mentality when competing. However, not all athletes have this, so there is a need to develop character and mental training for the athletes that are needed to be used to improve athlete performance.